PENERAPAN PEMASARAN DIGITAL PADA UMKM SEBLAK PRASMANAN BABEH - Barokah, Siti Barokah; Madhani, Desyia Aulia; Hidayatulloh, Hafid Syarif; Azzahra, Riska Diva (ICON Publisher, 2025)
This study aims to enhance the visibility and competitiveness of the UMKM Seblak Prasmanan Babeh through the implementation of a digital marketing strategy. Before the strategy implementation, this UMKM had minimal digital presence. The methods used included setting up Google Maps, creating an Instagram account, registering on GoFood, content creation tutorials, and content calendar planning. After implementing the strategy, the results showed a significant increase in business visibility. Listing the location on Google Maps resulted in more than 50 searches within the first week. The Instagram account @SeblakPrasmanan_Babeh demonstrated an increase in engagement and growth potential, although the number of followers was still low at the initial stage. The UMKM owner successfully uploaded three new promotional content pieces that captured customer attention. Overall, the initial results indicate that the digital marketing strategy has positively impacted the visibility of the UMKM. For optimal results, it is recommended that this strategy be further developed through consistent content calendar planning, optimization of other digital platforms, and regular evaluation in line with market dynamics.